Dichlorodiphenyltrichloroethane (DDT) and its metabolites in house dust, soil and selected food crops from indoor residual sprayed areas of Apac and Oyam Districts, Uganda - Mukasa, Paul; Wasswa, John; Namuyomba, Proscovia; Ntambi, Emmanuel (African Journal of Pure and Applied Chemistry, 2022)
Dichlorodiphenyltrichloroethane (DDT) levels and its metabolites are reported in 75 soil and 75 vegetable samples from the vicinity of homesteads sprayed with DDT during indoor residual spraying (IRS) pilot exercise, carried out in 2008 in Apac and Oyam districts, Uganda as a measure to control malaria. The samples were randomly and conveniently collected in 2020 from selected villages of the districts, extracted using solid dispersion and multi-residue methods for soil and vegetable samples, respectively and analyzed using GC-ECD and GC-MS. DDT residues were detected in all samples collected. The ΣDDT (μg kg-1) in all indoor house dust, outdoor soil samples from villages of Apac and Oyam districts and control areas were 69.9±20.9 and 8.9±4.7, 113.4±22.6 and 15.4±4.3, and 1.13±0.27 and 1.8±0.9, respectively. ΣDDT were significantly higher (p < 0.05) in the study areas than the control areas. In vegetables, ΣDDT (μg kg-1) ranged between 1.7±0.3 and 8.3±4.0 and 2.3±0.4 and 11.4±7.5 in the study and control areas, respectively. Abelmoschus esculentus and Gynandropsis gynandra had the highest levels. The results suggest that IRS had an effect on DDT levels in the environment. However, ΣDDT in vegetables were significantly below (P < 0.05) the EU EMRL, thus, the results raise no concern regarding the potential health effects of DDT to the residents. Nevertheless, due to bioaccumulation effects of DDT, to control malaria, measures like Eco health rather than IRS of DDT should be embraced.
Keywords: Dichlorodiphenyltrichloroethane metabolites; Indoor residual spraying.